An Evaluation of the Relationship Between Critical Thinking and Creative Thinking: Complementary Metacognitive Processes or Strange Bedfellows? - Christopher P. Dwyer; Deaglán Campbell; Niall Seery (Journal of Intelligence, 2025)
Though both critical thinking and creative thinking are often cited and promoted as important cognitive processes in personal, academic and professional settings, common misconceptualisation of both often leads to confusion for non-experts; for example, with respect to lumping them together erroneously as much the same thing, completely confusing them for one another or, on the other hand, distinguishing them to such an extent that all genuine overlap is ignored. Given the importance of these processes in real-world scenarios, quality education and ‘metaeducation’ is necessary to ensure their appropriate translation to students and educators, alike. Thus, the aim of the current review is to discuss various perspectives on both critical and creative thinking with particular focus paid to addressing such common misconceptualisation. Detailed discussion is provided with respect to important ways in which they are distinct and overlap. Recommendations for what contexts application of each are appropriate are also provided. Furthermore, implications for such enhanced understanding are discussed, in light of both theory and research.